Trend capital structure for the construction companies in Malaysia - Meriam, Suhaili (Universiti Malaysia Sarawak, (UNIMAS), 2003)
This paper attempts to start filling this gap in our knowledge. Our primary objective is to establish trend of capital structure for construction companies in Malaysia, the effect of leverage companies' financial performance and to established whether capital structure in construction companies is related to factors similar to those appearing to influence the capital structure in US firms